2015
DOI: 10.1063/1.4906875
|View full text |Cite
|
Sign up to set email alerts
|

HXeI and HXeH in Ar, Kr, and Xe matrices: Experiment and simulation

Abstract: Experimental and theoretical studies of HXeI and HXeH molecules in Ar, Kr, and Xe matrices are presented. HXeI exhibits the H–Xe stretching bands at 1238.0 and 1239.0 cm−1 in Ar and Kr matrices, respectively, that are blue-shifted from the HXeI band observed in a Xe matrix (1193 cm−1) by 45 and 46 cm−1. These shifts are larger than those observed previously for HXeCl (27 and 16 cm−1) and HXeBr (37 and 23 cm−1); thus, the matrix effect is stronger for less stable molecules. The results for HXeI are qualitativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…However, the energetic stabilization or destabilization of HNgY molecule by a matrix is still unclear; there are a few experimental studies on the environmental effects on HNgY molecules [14][15][16]. Khriachtchev et al studied relative stabilities of HXeOH and HXeOXeH in a Xe matrix at 55 K and found that HXeOXeH is more stable than HXeOH [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the energetic stabilization or destabilization of HNgY molecule by a matrix is still unclear; there are a few experimental studies on the environmental effects on HNgY molecules [14][15][16]. Khriachtchev et al studied relative stabilities of HXeOH and HXeOXeH in a Xe matrix at 55 K and found that HXeOXeH is more stable than HXeOH [17].…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy might originate from the fact that theoretical calculations are done for species in vacuum whereas the experiments are done for the species in the solid phase. There are some attempts to model the environmental effect on HNgY; e.g., on the H-Ng stretching frequencies of HNgY in different matrices [15,[19][20][21][22][23]. Among these studies, the methodology developed by Nakayama and co-workers could reproduce the experimentally observed order of H-Ng stretching frequencies [15,19].…”
Section: Introductionmentioning
confidence: 99%
“…The stress acting on HXeY would be an important factor affecting the vibrational shifts, which was also suggested by Kalinowski et al 19 We note in passing that the small stabilization energies in the Ne matrix (sometimes positive values) can be related to the rather structureless configurations of Ne atoms around HXeY. Also, as pointed out in the previous work, 31 it may be the reason for a failure to prepare HXeI in the Ne matrix experimentally. It is also interesting to note that the frequency shifts from the gas-phase values exhibit a trend Dn(HXeCCH) E Dn(HXeCl) o Dn(HXeBr) o Dn(HXeI) in the same Ng matrix environments.…”
Section: Hybrid Quantum-classical Simulations In the Solid Matricesmentioning
confidence: 79%
“…Similar observations have been made for HXeCl and HXeI in our previous studies. 28,31 As shown above in the frequency analysis of HXeY-Ng, the H-Xe stretching frequency is strongly affected by Ng atoms that are close to the hydrogen atom. In this situation, a displacement of the Ng atom toward the hydrogen atom results in a blue shift because the potential energy curve is quite repulsive when the Ng atom is located closer to the hydrogen atom.…”
Section: Hybrid Quantum-classical Simulations In the Solid Matricesmentioning
confidence: 94%
“…It is therefore most likely that the polarizable matrix enhances the charge separation in the molecule, blue-shiing the H-Ng stretching mode. This effect is predicted for a number of HNgY molecules by the polarized continuum model, 35 DFT calculations in noble-gas clusters, 36 and hybrid quantum-classical simulations, 37,38 although an opposite opinion has been derived from the MP4 method.…”
mentioning
confidence: 99%